Structural and allergenic properties of the fatty acid binding protein from shrimp Litopenaeus vannamei. Issue 5 (30th October 2021) - Múnera, Marlon; Martínez, Dalgys; Wortmann, Judith; Zakzuk, Josefina; Keller, Walter; Caraballo, Luis; Puerta, Leonardo
Abstract: Background: The shrimp Litopenaeus vannamei is an important source of food allergens but its allergenic repertoire is poorly characterized. Cross‐reactivity between crustacean and mites has been reported, with tropomyosin, the most relevant allergen involved. The aim of this study was to investigate the structural and immunological properties of a recombinant Fatty Acid Binding Protein (FABP) family from L . vannamei (LvFABP). Methods: ELISA, skin prick test (SPT) and basophil activation assays were performed to determine IgE reactivity and allergenic activity of LvFABP. LC‐MS/MS and Circular Dichroism experiments were done for structural analysis. B‐cell epitope mapping with overlapping peptides, and cross‐inhibition studies using human sera were done to identify antigenic regions and cross‐reactivity. Results: The recombinant LvFABP bound serum IgE from 27% of 36 shrimp allergic patients and showed allergenic activity when tested for basophil activation and SPT in a selected number of them. CD‐spectroscopy of LvFABP revealed that the protein is folded with a secondary structure composed of mainly β‐strands and a smaller fraction of α helices. This is consistent with molecular modelling results, which exhibit a typical β barrel fold with two α‐helices and ten β‐strands. Epitope mapping identified two IgE‐binding antigenic regions and inhibition assays found high cross‐reactivity between LvFABP and Blo t 13, mediated by the antigenic region involving amino acids 54 to 72. Conclusions: Our results show that LvFABP is a shrimp allergen that cross reacts with the house dust mite allergen Blo t 13 and has allergenic activity, which suggest that it could be clinically relevant in case of shellfish allergy. This new allergen, named Lit v 13, will also help to understand basic mechanisms of sensitization to shrimp. Abstract : The FABP from shrimp Litopenaeus vannamei (Lit v 13) showed 27% frequency of serum IgE reactivity in shrimp allergic subjects. The allergenic activity of Lit v 13 was demonstrated by SPT and BAT using flow cytometry. One B‐cell epitope involved in the high IgE cross‐reactivity between Lit v13 and Blo t 13 was identified.Abbreviations: 5G3 mAb, anti‐Blo t 3 monoclonal antibodes; BAT, basophil activation test; Blo t 13, Blomia tropicalis allergen of group 13 of house dust mite; FABP, fatty acid binding protein; Lit v 13, FABP from Litopenaeus vannamei ; OD, optical density; PBS, phosphate buffer saline; SPT, skin prick test.